2021
DOI: 10.1007/s00033-020-01449-8
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics and spatio-temporal patterns in a two-species chemotaxis system with two chemicals

Abstract: In this paper, we consider the signal-dependent diffusion and sensitivity in a chemotaxis-competition population system with two different signals in a two-dimensional bounded domain. We consider more general signal production functions and assume that the signal-dependent diffusion is a decreasing function which may be degenerate with respect to the density of the corresponding signal. We first obtain the global existence and uniform-in-time bound of classical solutions and show that the blow-up effect can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Predator-prey interaction is one of the basic interspecies relations in nature and society [3,6,11,26]. Because of environmental stochastic perturbations, more and more researchers are interest on the following stochastic predator-prey model driven by three independent Brownian motions W 1 (•), W 2 (•) and W 3 (•):…”
Section: Introductionmentioning
confidence: 99%
“…Predator-prey interaction is one of the basic interspecies relations in nature and society [3,6,11,26]. Because of environmental stochastic perturbations, more and more researchers are interest on the following stochastic predator-prey model driven by three independent Brownian motions W 1 (•), W 2 (•) and W 3 (•):…”
Section: Introductionmentioning
confidence: 99%
“…The presence of time delay makes it difficult to study the stability of the coexisting steady‐state solution of system (). Moreover, the spatially non‐homogeneity of the parameters in system () makes it impossible to discuss () as in the previous literature 22–29 . In Lou 30 and Cantrell and Cosner, 31 the existence of a positive steady‐state solution, as well as the effects of dispersal and spatial heterogeneity, is obtained for a logistic population model with a function m ( x ) representing the intrinsic growth rate of the species.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the spatially non-homogeneity of the parameters in system (2) makes it impossible to discuss (2) as in the previous literature. [22][23][24][25][26][27][28][29] In Lou 30 and Cantrell and Cosner, 31 the existence of a positive steady-state solution, as well as the effects of dispersal and spatial heterogeneity, is obtained for a logistic population model with a function m(x) representing the intrinsic growth rate of the species. The main reason for the introduction of the spatial variation in m(x) is to investigate how the favorable (i.e., m(x) > 0) and unfavorable (i.e., m(x) < 0) habitats affect the dynamics of population.…”
Section: Introductionmentioning
confidence: 99%
“…In this model the populations of predator and prey permanently oscillate for almost all positive initial conditions. Recently, there have been some excellent works on global dynamics of resource competitive models (see [4,5,11,16,17,19,24,22,25,30,31,32,33,34]), which are important in understanding of the mechanism of natural selection: the principle of competitive exclusion (see [1,3,10,26,27,28,35,36]) or the coexistence of competing species. For example, Volterra [29] observed that the coexistence of two or more predators competing for fewer prey resources is impossible.…”
mentioning
confidence: 99%